Analysis of a period of elevated ozone concentration reported over the Vaal Triangle on 2 June 2013 - Feig, G.; Ncipha, X.; Naidoo, S.; Mabaso, D.; Ngcukana, N.; Tshehla, C.; Masuku, N. (Clean Air Journal, 2014)
A peak in the ambient ozone concentration was observed at three of the six ambient air quality monitoring stations in the Vaal Triangle Airshed Priority Area on the second of June 2013. The ozone peak was associated with elevated concentrations of particulate matter, including PM10, PM2.5 and black carbon, but not sulphur dioxide, oxides of nitrogen, carbon monoxide nor benzene. Back trajectory analysis using Hysplit showed that the air masses containing the high levels of ozone passed over areas influenced by coal fired power stations in the Waterberg, metal processing in the Bojanala region and high intensity fires 30km to 50km upwind of the stations.